Force Model and Elastic Deformation Analysis of 20-High Sendzimir Mill Rolls - Wang, Z.H.; Lei, Y.L.; Feng, Y.H.; Hu, H.F. (Проблемы прочности, 2017)
A 20-high Sendzimir mill is widely used in cold rolling. The deformation of rolls within the roll system as a whole is analyzed without pin-pointing upon each roll and impact on the rolling process. The mechanical model of the work roll, first intermediate roll, second intermediate driven roll, and second intermediate idler roll was proposed and the contact force of each roll was calculated in the rolling process. The finite element model was constructed on the basis of calculation results, the elastic deformation of each roll was analyzed in three rolling passes. It was found that the resultant force of the work roll was the maximum of all rolls, and the maximum elastic deformation of each roll was observed in the second rolling pass; the radial elastic deformation of each roll would influence the plate, its quality, viz. an uneven strip thickness. Each roll is subjected to cyclic stress, so the bending deformation of roll can reduce its service life, producing the fatigue crack.